1995
DOI: 10.1002/app.1995.070560308
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interfacial FTIR spectroscopic studies of latexes. IX. The effect of homopolymer and copolymer structures on surfactant mobility in Sty/BA latices

Abstract: The effects of homopolymer and copolymer compositions and structures in styrene/n‐butyl acrylate (Sty/BA) latices on sodium dioctyl sulfosuccinate (SDOSS) surfactant mobility and its preferential concentration at the film–air (F–A) and film–substrate (F–S) interfaces were examined using attenuated total reflectance Fourier transform infrared (ATR FTIR) spectroscopy. It appears that the SDOSS concentration at the F–S interface is highest when the Sty/BA feed ratio is 50/50, and the excess of Sty results in migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…This behavior can be attributed to the ability of SDOSS molecules to migrate preferentially to- ward the F-A interface. Our previous studies 35,36 also indicated that SDOSS migrations are influenced by the surface tension of a substrate and the glass transition temperature (T g ) of the polymer/copolymer. For a higher styrene content, the T g is higher, and the rate of latex coalescence increases.…”
Section: Quantitative Analysis Of Surfactant In Latexesmentioning
confidence: 92%
See 3 more Smart Citations
“…This behavior can be attributed to the ability of SDOSS molecules to migrate preferentially to- ward the F-A interface. Our previous studies 35,36 also indicated that SDOSS migrations are influenced by the surface tension of a substrate and the glass transition temperature (T g ) of the polymer/copolymer. For a higher styrene content, the T g is higher, and the rate of latex coalescence increases.…”
Section: Quantitative Analysis Of Surfactant In Latexesmentioning
confidence: 92%
“…35 It appears that the latex stabilization may have a significant effect on the distribution of surfactant molecules across the coalesced latex and that their orientation changes depend upon the stage of coalescence and the water front's moving toward the surface. In these studies, it also became apparent that vibrational spectroscopy, in particular, ATR and step-scan photoacoustic (S 2 -PAS) FTIR spectroscopy, is a powerful tool in determining molecular level features occurring near interfacial regions in latex films.…”
Section: Surfactant Behavior In Latex Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not, because it determines the mechanisms by which the surfactant will be distributed in the final latex film. And surfactant distributions are extensively studied nowadays because of their strong influence on properties of latex films (18)(19)(20).…”
mentioning
confidence: 99%